The gender wage gap among medical specialists: a quantitative analysis of the hourly pay of publicly employed senior doctors in New Zealand. Issue 4 (27th April 2021) - Sin, Isabelle; Bruce-Brand, Bronwyn; Chambers, Charlotte Nesta Louise
Abstract : Objectives: To estimate the gender gap in hourly wages earned by medical specialists in their main jobs after controlling for age, number of hours worked and medical specialty. Design: Observational using governmental administrative and survey data. Setting: New Zealand public employed medical workforce. Participants: 3510 medical specialists who were employed for wages or a salary in a medical capacity by a New Zealand district health board (DHB) at the time of the March 2013 census, whose census responses on hours worked were complete and can be matched to tax records of earnings to construct hourly earnings. Main outcome measures: Hourly earnings in the DHB job calculated from usual weekly hours worked reported in the census and wage or salary earnings paid in the month recorded in administrative tax data. Results: In their DHB employment, female specialists earned on average 12.5% lower hourly wages than their male counterparts of the same age, in the same specialty, who work the same number of hours (95% CI 9.9% to 15.1%). Adding controls for a wide range of personal and work characteristics decreased the estimated gap only slightly to 11.2% (95% CI 8.6% to 13.8%). At most, 4.5 percentage points can be explained by gender differences in experience at the same age. Conclusions: Male specialists earn a large and statistically significant premium over their female colleagues. Age, specialty and hours of work do not appear to drive these wage gaps. These findings suggest that employment agreements that specify minimum wages for each level of experience, and progression through these levels, are insufficient to eliminate gender wage gaps between similar men and women with the same experience.